Method for producing transparent conductive film
The transparent conductive film with a surface-treated metal nanowire layer addresses the issues of conductivity loss in flexible applications and resistance uniformity, achieving excellent performance in both aspects.
Patent Information
- Application Number
- JP2020148153
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-03
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2040-09-03
AI Technical Summary
Existing transparent conductive films with metal oxide layers suffer from loss of conductivity when bent, making them unsuitable for flexible applications, and those with metal nanowires face issues with electrical resistance uniformity.
A transparent conductive film is developed with a substrate and a surface-treated transparent conductive layer containing metal nanowires, which are dispersed uniformly to ensure excellent in-plane electrical resistance uniformity.
The film achieves excellent electrical resistance uniformity and high light transmittance, making it suitable for flexible applications while maintaining conductivity.
Smart Images

Figure 0007663328000002 
Figure 0007663328000003 
Figure 0007663328000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a transparent conductive film. [Background technology]
[0002] Conventionally, in image display devices having touch sensors, transparent conductive films obtained by forming a metal oxide layer such as ITO (indium tin oxide) on a transparent resin film have been widely used as electrodes for the touch sensors. However, transparent conductive films having such metal oxide layers tend to lose conductivity when bent, making them difficult to use in flexible displays and other applications. However, there is a problem that it is difficult to use in applications where high flexibility is required.
[0003] A transparent conductive film having a transparent conductive layer containing metal nanowires is known as a highly flexible transparent conductive film. Metal nanowires are wire-shaped conductive materials with nanometer-sized diameters. In a transparent conductive layer made of metal nanowires, the metal nanowires are in a mesh shape, so that a good electrical conduction path is formed with a small amount of metal nanowires, and openings are formed in the gaps of the mesh, thereby achieving high light transmittance.
[0004] On the other hand, in transparent conductive films, uniformity in the electrical resistance is required, and in transparent conductive layers containing such metal nanowires, uneven distribution of the metal nanowires causes a problem of variation in electrical resistance. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Special Publication No. 2009-505358 [Patent Document 1] Patent No. 6199034 Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention has been made to solve the above problems, and an object of the present invention is to provide a transparent conductive film that contains metal nanowires and has excellent uniformity in electrical resistance. [Means for solving the problem]
[0007] The transparent conductive film of the present invention comprises a substrate and a transparent conductive layer disposed on at least one side of the substrate, the surface of the substrate facing the transparent conductive layer being a surface-treated surface, and the transparent conductive layer containing metal nanowires. In one embodiment, the transparent conductive layer is disposed directly on the substrate. In one embodiment, the substrate comprises a substrate film. In one embodiment, the substrate has a single layer structure. In one embodiment, the substrate includes a hard coat layer disposed on at least one side of a substrate film, and the transparent conductive layer is disposed on the hard coat layer side of the substrate. In one embodiment, the dispersion of the surface resistance value of the transparent conductive film is 10 [(Ω / □) 2 ]below. In one embodiment, the surface treatment is a plasma treatment or a corona treatment. In one embodiment, the base film is made of a polyester resin or a cycloolefin resin. In one embodiment, the metal nanowires are silver nanowires. In one embodiment, the contact angle of the treated surface of the substrate with water is 90° or less. Effect of the Invention
[0008] According to the present invention, it is possible to provide a transparent conductive film that contains metal nanowires and has excellent uniformity in electrical resistance. [Brief description of the drawings]
[0009] [Figure 1] 1 is a schematic cross-sectional view of a transparent conductive film according to one embodiment of the present invention. [Diagram 2] 1 is a schematic cross-sectional view of a transparent conductive film according to another embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] A. Overview of transparent conductive films FIG 1 is a schematic cross-sectional view of a transparent conductive film according to one embodiment of the present invention. A transparent conductive film 100 according to this embodiment includes a substrate 10 and a transparent conductive layer 20 disposed on at least one side of the substrate 10. FIG 2 is a schematic cross-sectional view of a transparent conductive film according to another embodiment. In a transparent conductive film 200 according to this embodiment, the substrate 10' has a two-layer structure, and includes a substrate film 11 and a hard coat layer 12 disposed on at least one side of the substrate film 11. In this embodiment, the transparent conductive layer 20 is disposed on the hard coat layer 12 side of the substrate 10'.
[0011] The transparent conductive layer 20 includes metal nanowires.
[0012] The surface of the substrate 10 facing the transparent conductive layer 20 is a surface-treated surface. In the present invention, the transparent conductive layer can be formed by coating a dispersion of metal nanowires, and by surface-treating the substrate 10, aggregation of the metal nanowires in the coating layer of the dispersion is suppressed, and the coating thickness of the dispersion becomes uniform, resulting in a transparent conductive film with excellent in-plane uniformity of resistance value (sheet resistance value).
[0013] Preferably, the transparent conductive layer is disposed directly on the substrate (i.e., without any other layer). Although not shown, the transparent conductive film may further include any other appropriate layer on the opposite side of the transparent conductive layer from the substrate. For example, a protective layer made of any appropriate organic material (e.g., curable resin, conductive resin) or inorganic material (e.g., silica, alumina, etc.) may be disposed.
[0014] In one embodiment, the transparent conductive film may be in a long shape.
[0015] The surface resistance of the transparent conductive film is preferably 0.1Ω / □ to 1000Ω / □, more preferably 0.5Ω / □ to 300Ω / □, and particularly preferably 1Ω / □ to 200Ω / □. The surface resistance can be measured by an eddy current method using a non-contact surface resistance meter (product name "EC-80") manufactured by Napson Corporation. The surface resistance can be the average value of five randomly selected points.
[0016] The dispersion of the surface resistance value of the transparent conductive film is preferably 10[(Ω / □) 2 ] or less, and more preferably 8 [(Ω / □) 2 ] or less, and more preferably 5 [(Ω / □) 2 The variance is calculated from five randomly selected measurements.
[0017] The haze value of the transparent conductive film is preferably 20% or less, more preferably 10% or less, and further preferably 0.1% to 5%.
[0018] The total light transmittance of the transparent conductive film is preferably 30% or more, more preferably 35% or more, and particularly preferably 40% or more.
[0019] B. Base material As described above, the substrate may have a single layer structure or a double layer structure. It may also have a multi-layer structure of three or more layers. A substrate having a single layer structure may be composed of a substrate film. In one embodiment, a substrate having a multi-layer structure is composed of a substrate film and a hard coat layer. The thickness of the substrate is preferably 20 μm to 220 μm, more preferably 30 μm to 120 μm. The total light transmittance of the substrate is preferably 30% or more, more preferably 35% or more, and further preferably 40% or more.
[0020] As described above, at least one surface of the substrate (the substrate film surface or the hard coat layer surface) is subjected to a surface treatment, such as a plasma treatment or a corona treatment.
[0021] Specifically, the plasma treatment may be a plasma treatment using oxygen, nitrogen, hydrogen, carbon dioxide, carbon tetrachloride, a fluorine compound, an inert gas, or a mixture of these as a reactive gas. The conditions of the plasma treatment may be set to any appropriate conditions depending on the type of the substrate, etc. The plasma emission amount may be, for example, 1 W to 2000 W, and the treatment speed may be, for example, 3000 mm / min to 2000 mm / min.
[0022] The conditions of the corona treatment may be set to any appropriate conditions depending on the type of substrate, etc. The irradiation energy in the corona treatment is, for example, 6 kW min / m 2 ~150kW·min / m 2 It is.
[0023] The contact angle of water on the surface-treated surface of the substrate is preferably not more than 90°, more preferably from 50° to 90°, and even more preferably from 60° to 85°. If within such a range, the above-mentioned effects of the present invention become prominent.
[0024] Any suitable material may be used as the material constituting the substrate film. Specifically, for example, a polymer film is preferably used. The material constituting the substrate film is typically a polymer film mainly composed of a thermoplastic resin. Examples of the thermoplastic resin include polyester resins; cycloolefin resins such as polynorbornene; acrylic resins; polycarbonate resins; and cellulose resins. Among them, polyester resins, cycloolefin resins, and acrylic resins are preferred. These resins are excellent in transparency, mechanical strength, thermal stability, and moisture shielding properties. The thermoplastic resins may be used alone or in combination of two or more kinds. In addition, optical films such as those used in polarizing plates, such as low retardation films, high retardation films, and brightness-improving films, can also be used as substrate films.
[0025] In one embodiment, the substrate film may be made of a polyester resin or a cycloolefin resin, and may be an optical film. By using such a material, a conductive film with excellent transparency can be obtained.
[0026] The thickness of the base film is preferably 20 μm to 200 μm, and more preferably 30 μm to 150 μm.
[0027] The total light transmittance of the above-mentioned base film is preferably 30% or more, more preferably 35% or more, and further preferably 40% or more.
[0028] The hard coat layer preferably has sufficient surface hardness, excellent mechanical strength, and excellent light transmittance. The hard coat layer can be formed from any suitable resin as long as it has such desired properties. Specific examples of the resin include thermosetting resin, thermoplastic resin, ultraviolet curing resin, electron beam curing resin, and two-liquid mixture resin. UV curing resin is preferred. This is because it can form a hard coat layer with simple operation and high efficiency.
[0029] Specific examples of ultraviolet curing resins include polyester-based, acrylic-based, urethane-based, amide-based, silicone-based, and epoxy-based ultraviolet curing resins. The ultraviolet curing resins include ultraviolet curing monomers, oligomers, and polymers. A preferred ultraviolet curing resin is a resin composition containing an acrylic monomer or oligomer component having preferably two or more, more preferably three to six, ultraviolet polymerizable functional groups. Typically, the ultraviolet curing resin contains a photopolymerization initiator.
[0030] The hard coat layer can be formed by any suitable method. For example, the hard coat layer can be formed by coating a resin composition for forming a hard coat layer on a substrate film, drying the composition, and curing the dried coating film by irradiating it with ultraviolet light.
[0031] The hard coat layer has a thickness of, for example, 0.1 μm to 20 μm, preferably 0.5 μm to 15 μm, more preferably 0.5 μm to 10 μm, and further preferably 0.5 μm to 5 μm.
[0032] The total light transmittance of the hard coat layer is preferably 30% or more, more preferably 35% or more, and further preferably 40% or more.
[0033] C.Transparent conductive layer As described above, the transparent conductive layer includes metal nanowires. Preferably, the transparent conductive layer further includes a binder resin.
[0034] The transparent conductive layer has a thickness of 1000 nm or less, preferably 800 nm or less, more preferably 600 nm or less, further preferably 30 nm to 500 nm, and particularly preferably 30 nm to 300 nm.
[0035] The total light transmittance of the transparent conductive layer is preferably 80% or more, preferably 85% or more, more preferably 90% or more, and further preferably 95% or more.
[0036] C-1. Metal nanowires Metal nanowires are conductive materials made of metal, shaped like needles or threads, and with a diameter of nanometers. Metal nanowires may be straight or curved. By using a transparent conductive layer made of metal nanowires, the metal nanowires can be in a mesh shape, so that even a small amount of metal nanowires can form a good electrical conduction path, and a transparent conductive film with low electrical resistance can be obtained. Furthermore, by forming the metal nanowires in a mesh shape, openings can be formed in the gaps of the mesh, and a transparent conductive film with high light transmittance can be obtained.
[0037] The ratio of the thickness d to the length L of the metal nanowire (aspect ratio: L / d) is preferably 10 to 100,000, more preferably 50 to 100,000, and particularly preferably 100 to 10,000. By using metal nanowires with such a large aspect ratio, the metal nanowires can be well crossed, and a small amount of metal nanowires can exhibit high conductivity. As a result, a transparent conductive film with high light transmittance can be obtained. In this specification, the "thickness of the metal nanowire" means the diameter when the cross section of the metal nanowire is circular, means the minor axis when the cross section is elliptical, and means the longest diagonal when the cross section is polygonal. The thickness and length of the metal nanowire can be confirmed by a scanning electron microscope or a transmission electron microscope.
[0038] The thickness of the metal nanowires is preferably less than 500 nm, more preferably less than 200 nm, particularly preferably 10 to 100 nm, and most preferably 10 to 50 nm. Within such a range, a transparent conductive layer with high light transmittance can be formed.
[0039] The length of the metal nanowires is preferably 1 μm to 1000 μm, more preferably 10 μm to 500 μm, and particularly preferably 20 μm to 100 μm. If the length is within this range, a transparent conductive film with high conductivity can be obtained.
[0040] As the metal constituting the metal nanowire, any appropriate metal can be used as long as it is a conductive metal. Examples of the metal constituting the metal nanowire include silver, gold, copper, Nickel and the like can be used. Materials obtained by plating these metals (for example, gold plating) can also be used. Among these, silver, copper, or gold are preferable from the viewpoint of electrical conductivity, and silver is more preferable.
[0041] Any suitable method may be adopted as the method for producing the metal nanowires. For example, a method of reducing silver nitrate in a solution, a method of applying a voltage or current from the tip of a probe to the surface of a precursor, drawing out the metal nanowire at the tip of the probe, and continuously forming the metal nanowire may be mentioned. In the method of reducing silver nitrate in a solution, silver nanowires may be synthesized by liquid-phase reduction of a silver salt such as silver nitrate in the presence of a polyol such as ethylene glycol and polyvinylpyrrolidone. Silver nanowires of uniform size can be mass-produced according to the methods described in, for example, Xia, Y.etal., Chem.Mater.(2002), 14, 4736-4745, and Xia, Y.etal., Nano letters(2003)3(7), 955-960.
[0042] The content of the metal nanowires in the transparent conductive layer is preferably 30 to 98 parts by weight, more preferably 40 to 85 parts by weight, relative to 100 parts by weight of the binder resin constituting the transparent conductive layer. If the content is within this range, a transparent conductive film having excellent electrical conductivity and light transmittance can be obtained.
[0043] C-2. Binder resin Any suitable resin can be used as the binder resin. Examples of the resin include acrylic resins, polyester resins such as polyethylene terephthalate, aromatic resins such as polystyrene, polyvinyl toluene, polyvinyl xylene, polyimide, polyamide, and polyamideimide, polyurethane resins, epoxy resins, polyolefin resins, acrylonitrile-butadiene-styrene copolymers (ABS), cellulose, silicone resins, polyvinyl chloride, polyacetate, polynorbornene, synthetic rubber, and fluorine resins. The binder resins may be used alone or in combination.
[0044] In one embodiment, a curable resin is used as the binder resin. For example, the curable resin may be a polyfunctional acrylic resin. The curable resin may be obtained from a monomer composition containing a polyfunctional monomer. Examples of polyfunctional monomers include tricyclodecane dimethanol diacrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane triacrylate, pentaerythritol tetra(meth)acrylate, dimethylolpropane tetraacrylate, dipentaerythritol hexa(meth)acrylate, 1,6-hexanediol (meth)acrylate, 1,9-nonanediol diacrylate, 1,10-decanediol (meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, dipropylene glycol diacrylate, isocyanuric acid tri(meth)acrylate, ethoxylated glycerin triacrylate, and ethoxylated pentaerythritol tetraacrylate. The polyfunctional monomers may be used alone or in combination.
[0045] The monomer composition may further contain a monofunctional monomer. When the monomer composition contains a monofunctional monomer, the content of the monofunctional monomer is preferably 40 parts by weight or less, more preferably 20 parts by weight or less, based on 100 parts by weight of the monomer in the monomer composition.
[0046] Examples of the monofunctional monomer include ethoxylated o-phenylphenol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, 2-ethylhexyl acrylate, lauryl acrylate, isooctyl acrylate, isostearyl acrylate, cyclohexyl acrylate, isophoronyl acrylate, benzyl acrylate, 2-hydroxy-3-phenoxy acrylate, acryloylmorpholine, 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and hydroxyethyl acrylamide. In one embodiment, a monomer having a hydroxyl group is used as the monofunctional monomer.
[0047] D. Manufacturing method of transparent conductive film The transparent conductive film can be formed by applying a transparent conductive layer-forming composition onto the surface-treated surface of the substrate. In one embodiment, the transparent conductive layer-forming composition contains a binder resin (or a monomer that forms the binder resin) and metal nanowires.
[0048] The composition for forming a transparent conductive layer includes metal nanowires. In one embodiment, the composition for forming a transparent conductive layer is prepared by dispersing the metal nanowires in any appropriate solvent. Examples of the solvent include water, alcohol-based solvents, ketone-based solvents, ether-based solvents, hydrocarbon-based solvents, and aromatic solvents. The composition for forming a transparent conductive layer may further include additives such as a resin (binder resin), a conductive material other than the metal nanowires (e.g., conductive particles), and a leveling agent. The composition for forming a transparent conductive layer may also include additives such as a plasticizer, a heat stabilizer, a light stabilizer, a lubricant, an antioxidant, an ultraviolet absorber, a flame retardant, a colorant, an antistatic agent, a compatibilizer, a crosslinking agent, a thickener, inorganic particles, a surfactant, and a dispersant.
[0049] The viscosity of the composition for forming a transparent conductive layer is preferably 5 mP·s / 25°C to 300 mP·s / 25°C, and more preferably 10 mP·s / 25°C to 100 mP·s / 25°C. Within this range, the effect obtained by setting the air direction in a specific direction in the air blowing step is greater. The viscosity of the composition for forming a transparent conductive layer can be measured using a rheometer (e.g., MCR302 by Anton Paar).
[0050] The dispersion concentration of the metal nanowires in the composition for forming a transparent conductive layer is preferably 0.01% by weight to 5% by weight. If it is in this range, the effects of the present invention become prominent.
[0051] Any suitable method may be adopted as a method for applying the composition for forming a transparent conductive layer. Examples of the application method include spray coating, bar coating, roll coating, die coating, inkjet coating, screen coating, dip coating, letterpress printing, intaglio printing, and gravure printing. Any suitable method (e.g., natural drying, air drying, heat drying) may be adopted as a method for drying the coating layer. For example, in the case of heat drying, the drying temperature is typically 100°C to 200°C, and the drying time is typically 1 to 10 minutes.
[0052] The coating layer preferably has a basis weight of 0.3 g / m 2 ~30g / m 2 and more preferably 1.6 g / m 2 ~16g / m 2 It is. EXAMPLES
[0053] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The evaluation methods in the examples are as follows. The thickness was measured using a scanning electron microscope "S-4800" manufactured by Hitachi High-Technologies Corporation after embedding in epoxy resin and cutting with an ultramicrotome to form a cross section.
[0054] (1) Surface resistance The surface resistance of the transparent conductive film (transparent conductive layer side) was measured by an eddy current method using a non-contact surface resistance meter (product name "EC-80") manufactured by Napson Corporation. The measurement temperature was 23°C. Measurements were performed at five randomly selected points, and the average of the measured values was taken as the surface resistance of the transparent conductive film obtained in the examples and comparative examples. In addition, the variance of the surface resistance was calculated from the measured values.
[0055] (2) Contact angle The substrate film used in the production of the transparent conductive film was placed on a slide glass with the surface-treated surface (one of the surfaces in the comparative example) facing up, and the contact angle of the surface-treated surface (one of the surfaces in the comparative example) with pure water was measured. 2 μl of pure water was dropped onto the surface-treated surface (one of the surfaces in the comparative example), and the contact angle was measured after 5 seconds (N=5). The contact angle was measured using a contact angle meter (manufactured by Kyowa Interface Co., Ltd., product name "CX-A type") in an atmosphere of 23° C. and 50% RH.
[0056] [Production Example 1] Preparation of composition for forming transparent conductive layer Silver nanowires were synthesized based on the method described in Chem. Mater. 2002, 14, 4736-4745. The silver nanowires obtained above were dispersed in pure water to a concentration of 0.2% by weight, and dodecyl-pentaethylene glycol was dispersed to a concentration of 0.1% by weight, to obtain a composition for forming a transparent conductive layer.
[0057] [Example 1] A cycloolefin film (manufactured by Zeon Corporation, product name "ZEONOR") was prepared as a substrate film, and the film was subjected to a surface treatment to obtain substrate A. The surface treatment was performed using a direct / remote dual-use atmospheric pressure plasma surface treatment experimental device (model name: AP-T05-S440) manufactured by Sekisui Chemical Co., Ltd., with the discharge electrode length L = 2 mm, film speed V = 5000 mm / min, discharge voltage = 115 V, and discharge current 0.1 A or less. While the substrate was transported using a transport roll, the composition for forming a transparent conductive layer prepared in Production Example 1 was applied onto the substrate using a bar coater (manufactured by Daiichi Rika Co., Ltd., product name "Bar Coater No. 16") to a thickness of 0.015 g / m 2 Thereafter, the coating layer was dried while transporting the substrate on which the coating layer was formed, to form a transparent conductive layer, thereby obtaining a transparent conductive film including the substrate and the transparent conductive layer. The obtained transparent conductive film was subjected to the above evaluations (1) and (2). The results are shown in Table 1.
[0058] [Example 2] A transparent conductive film was obtained in the same manner as in Example 1, except that a polyester resin film (manufactured by Mitsubishi Chemical Corporation) was used as the base film. The obtained transparent conductive film was subjected to the above-mentioned evaluations (1) and (2). The results are shown in Table 1.
[0059] [Example 3] A transparent conductive film was obtained in the same manner as in Example 1, except that a cellulose triacetate film (manufactured by Konica Minolta Advanced Layer, product name "KC4UY") was used as the base film. The obtained transparent conductive film was subjected to the above evaluations (1) and (2). The results are shown in Table 1.
[0060] [Example 4] A cellulose triacetate film (manufactured by Konica Minolta Advanced Layers, product name "KC4UY") was prepared as a substrate film, and a hard coat layer (thickness: 10 μm) was formed on the substrate film to obtain a substrate (substrate film / hard coat layer). The hard coat layer was formed by applying a composition for forming a hard coat layer prepared as described below to a substrate film to form a coating layer, heating the coating layer at 90° C. for 1 minute, and irradiating the heated coating layer with ultraviolet light (200 mJ / cm 2 ) to cure the coating layer. Furthermore, the surface of the substrate on which the hard coat layer was formed was subjected to a surface treatment in the same manner as in Example 1 to obtain a substrate B. While the substrate was being transported using a transport roll, the composition for forming a transparent conductive layer prepared in Production Example 1 was applied onto the hard coat layer using a bar coater (manufactured by Daiichi Rika Co., Ltd., product name "Bar Coater No. 16") to a thickness of 0.015 g / m 2 Thereafter, the coating layer was dried while transporting the substrate on which the coating layer was formed, to form a transparent conductive layer, thereby obtaining a transparent conductive film including the substrate and the transparent conductive layer. The obtained transparent conductive film was subjected to the above evaluations (1) and (2). The results are shown in Table 1. (Preparation of hard coat layer forming composition) A composition for forming a hard coat layer was prepared by mixing 31 parts of a 15-functional urethane acrylic oligomer (manufactured by Shin-Nakamura Chemical Co., Ltd., product name: NK Oligo UA-53H, weight average molecular weight: 2300), 39 parts of pentaerythritol triacrylate (PETA) (manufactured by Osaka Organic Chemical Industry Co., Ltd., product name: Viscoat #300), 30 parts of ethoxylated glycerin triacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd., product name: NK Ester A-GLY-9E), and 3 parts of a photopolymerization initiator (manufactured by Ciba Japan Co., Ltd., product name: Irgacure 907) and diluting with methyl isobutyl ketone to a solids concentration of 40%.
[0061] [Comparative Example 1] A transparent conductive film was obtained in the same manner as in Example 1, except that the surface treatment by discharge was not performed. The obtained transparent conductive film was subjected to the above-mentioned evaluations (1) and (2). The results are shown in Table 1.
[0062] [Comparative Example 2] A transparent conductive film was obtained in the same manner as in Example 2, except that the surface treatment by discharge was not performed. The obtained transparent conductive film was subjected to the above-mentioned evaluations (1) and (2). The results are shown in Table 1.
[0063] [Comparative Example 3] A transparent conductive film was obtained in the same manner as in Example 3, except that the surface treatment by discharge was not performed. The obtained transparent conductive film was subjected to the above-mentioned evaluations (1) and (2). The results are shown in Table 1.
[0064] [Comparative Example 4] A transparent conductive film was obtained in the same manner as in Example 4, except that the surface treatment by discharge was not performed. The obtained transparent conductive film was subjected to the above-mentioned evaluations (1) and (2). The results are shown in Table 1.
[0065] [Table 1] [Explanation of symbols]
[0066] 10 Base material 20 Transparent conductive layer 100, 200 Transparent conductive film
Claims
1. A substrate and a transparent conductive layer disposed on at least one side of the substrate, the surface of the substrate facing the transparent conductive layer is a surface-treated surface, the transparent conductive layer comprises metal nanowires; The contact angle of the surface-treated surface of the substrate with water is 60° to 85°. Transparent conductive film.
2. The transparent conductive film according to claim 1 , wherein the transparent conductive layer is disposed directly on the substrate.
3. The transparent conductive film according to claim 1 , wherein the substrate comprises a substrate film.
4. The transparent conductive film according to claim 1 , wherein the substrate has a single layer structure.
5. The substrate further comprises a hard coat layer disposed on at least one side of the substrate film; the transparent conductive layer is disposed on the hard coat layer side of the substrate; The transparent conductive film according to claim 3 .
6. The dispersion of the surface resistance is 10 [(Ω / □) 2 6. The transparent conductive film according to claim 1, wherein the thickness of the transparent conductive film is equal to or less than 100 nm.
7. The transparent conductive film according to claim 1 , wherein the surface treatment is a plasma treatment or a corona treatment.
8. The transparent conductive film according to claim 3 , wherein the substrate film is made of a polyester resin or a cycloolefin resin.
9. The transparent conductive film according to claim 1 , wherein the metal nanowires are silver nanowires.
Citation Information
Patent Citations
Steamer
JP1986099034A
Transparent conductors based on nanowires
JP2009505358A
Substrate for conductive material with inorganic thin film, substrate with transparent electrode, and production method of the same
JP2014019038A
Transparent conductive film and method for producing the same
JP2014096369A
Conductive sheet and touch panel using the same
JP2014153784A